Problematika Penetapan Penyidik Komisi Pemberantasan Korupsi - Imran Imran; Indra Yudha Koswara (CV. Social Politic Genius (SIGn), 2023)
This study aims to examine the problems of appointing Commission investigators. This study uses normative legal research with a statute approach. The collected legal material is then qualitatively analyzed to describe the problem and answer the study objectives. The results show that the Commission holds the authority to appoint Civil Servant Investigators from its internal ranks. One of the requirements for such an appointment is that the Commission conducts education and training in the field of investigation in collaboration with the Police. However, the Commission still recruits investigators from the Police and the Attorney General’s Office. Appointing investigators from these two entities presents challenges, including continuity issues in the investigative process, the risk of losing essential information or knowledge about handled cases, and legal and administrative considerations when the tenure of an employed investigator reaches its maximum limit. Therefore, it is recommended that the Commission and relevant stakeholders enhance the capacity and competency of internal Civil Servant Investigators through systematic and continuous education and training, thus reducing dependence on investigators from the Police and the Attorney General’s Office. Furthermore, the Commission should consider formulating strategies to minimize the risk of vital information loss due to investigator turnover, such as creating detailed case documentation and an effective case transition system. Additionally, the Commission can collaborate with relevant legal and administrative entities to address potential legal and administrative issues arising from the conclusion of an investigator’s tenure, considering aspects of justice and thoroughness in the investigative process.